CLASSIFICATION AND PROTECTION OF THE RIGHTS OF CREDITORS IN BANKRUPTCY CASES - Yuldashev, Serhiy O.; Kozyreva, Valentyna P. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article investigates up-to-date issues of the institute’s development of competitive creditors. Some types of creditors are classified according to the Code of Bankruptcy Procedures, and the Law of Ukraine «On Restoration of the Debtor’s Solvency or Recognition as a Bankrupt», and their rights to ensure claims. Methods of research: a set of general and special methods of scientific knowledge – terminological, logical-semantic, comparative, system-structural, logical-normative. Results: the analysis of the current situation regarding the illustration of domestic normative sources in accordance with the Code of Bankruptcy procedures suggests that in order to protect the rights of creditors, the Code enhances their rights and improves their terms of participation in the bankruptcy procedure. Creditors can now initiate a bankruptcy case, participate in voting in decision-making. Also, a creditor may demand a court the decision to terminate the moratorium on its claims regarding the collateral. Key powers in bankruptcy cases are transferred from the creditors committee to the creditors meeting. If the first meeting of creditors is not considered to be hold due to the non-arrival of creditors with a sufficient number of votes, it may be possible to hold other meeting with the reduced quorum. Discussion: the main realities of the domestic legislative and regulatory framework, which need improvement, are proposed to be divided into separate groups of registers, current and privileged creditors with their internal delimitation.